The Effectiveness Of Iccwl In Reducing Misconceptions And Supporting Decision Making And Problem-Solving Skills Of Form 2 Students - Chandrakesan, Kasturi (2021)
Climate change is one of the biggest challenges of humankind in this century. There is an urgent need to foster climate change awareness and knowledge among young people to preserve the environment for the future generation. Education is an essential element of the global response to climate change. The purpose of this study is to measure the effect of interactive climate change web-based learning (ICCWL) in overcoming misconceptions about climate change on the Greenhouse effect (GHE), Global warming (GW), Acid rain (AR) and Ozone layer depletion (OLD), enhancing the ability to make decisions and to solve problems on climate change among Form Two students. A total of 123 Form Two students from a suburban school in Malaysia involved in this study. The participating was school randomly identified from the population of 27 secondary schools in Kulim district. The students were randomly assigned to experimental and control groups. The experimental group consisted of 63 students; the control group consisted of 60 students. The research used both intervention mixed-method design and qualitative methods. The study performed in three stages. In the first stage, interviews were conducted with students and teachers and followed by the document analysis to design the Interactive Climate Change Web Learning (ICCWL). In the second stage, the effects of the treatment on misconceptions and decision-making ability were measured. For this purpose, the Atmosphere Related Environmental Problem Diagnostic Test (AREPDiT) and Decision-making Questionnaire (DMQ) were administered during pre and post-tests.